Animal Metaphors in Indonesian and English - Ardik Ardianto (LPPM Universitas Terbuka, 2022)
This paper is a contrastive semantic analysis exploring the concept of animal metaphors in Indonesian and English by means of three contrastive elements, i.e., the universality of form and meaning, the universality of meaning albeit different forms, and the element of distinctiveness or idiosyncrasy of each language. All data were obtained from Indonesian Idioms and Expressions, Oxford Dictionary of Idioms, Indonesian Proverbs Dictionary, and Kamus Besar Bahasa Indonesia. The data were classified and analysed based on the three contrastive elements. Subsequently, each element was scrutinised in terms of the rationality embedded therein. The results of careful analysis show that the universality of the form and meaning of animal metaphors in both languages (i.e., Indonesian and English) reflects the common thread of harmonisation of language expressions—although in some other points, the perception is completely of difference between Indonesian speakers and English ones and hence creates contrasting forms of linguistic expression. The distinctive element of metaphors in each language illustrates that other extra-linguistic elements, e.g., history, values, norms, customs, and to name a few, contribute greatly to the process of constructing language expressions.